Temperature dependence of the optical band gap and refractive index of poly(ethylene terepthalate) oligomer-DDQ complex thin film - Yakuphanoğlu, Fahrettin; Arslan, M; Küçükislamoglu, M; Zengin, M (Pergamon-Elsevier Science Ltd, 2005)
The temperature dependence of the optical band gap and refractive index dispersion of thin film of poly(ethylene terepthalate) oligomer-DDQ charge transfer complex has been investigated. The absorption edge shifts to the lower energy as consequence of the thermal annealing on film and the fundamental absorption edge corresponds to a direct energy gap. The temperature coefficient of the optical band gap for the film was found as dE(g)/dT 3.15 x 10(-3) eV/K. The temperature dependence of the refractive index has also been investigated and it is observed that the refractive index changes by annealing temperatures. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: thin film; optical band gap; refractive index dispersion; solar energy